A comparative study of single layer versus double layer small bowel anastomosis - Modi, Jenishkumar Vijaykumar; Puwar, Namrata (International Surgery Journal, 2023)
Background: There are various gastrointestinal surgeries in which we require small bowel anastomosis. Bowel anastomosis is quite common in different bowel pathology. Bowel anastomosis can be done by hand sewn or y stapler. In hand sewn anastomosis, we can do single layer or double layer anastomosis. Method: The study was carried out in 50 patients between August 2019 to March 2020. In this study, we have included all the patients who require small bowel end to end anastomosis in either elective surgeries or emergency surgeries. Patients who require proximal stoma formation and other than small bowel anastomosis are excluded. In present study, patients were randomly allocated in two groups: group A (n=25) includes single layer(interrupted) hand sewn bowel anastomosis and group B two layer (Connell and seromuscular) handsewn bowel anastomosis. Author have compared two groups in terms of intraoperative time and postoperative leak. Results: This shows that there is significantly reduce in intraoperative time in group A patient while there is no significant difference in postoperative complication or postoperative leak between two groups. Conclusions: There is no significant difference in single layer and double layer technique of bowel anastomosis.